The prevalence of enamel opacities in permanent teeth of 11-12 year-old school children in Kuala Lumpur, Malaysia - Yusoff, N.; Jaafar, N.; Razak, I.A.; Chew, Y.Y.; Ismail, N.; Bulgiba, A.M. (2008)
Objective To determine the prevalence, distribution, severity and treatment need of enamel opacities among 11-12 year-old school children in a fluoridated urban community. Design A cross-sectional descriptive survey of enamel opacities in 11-12 year-old schoolchildren. Clinical setting A questionnaire survey and a clinical examination of erupted teeth using the Modified DDE Index was conducted on schoolchildren in randomly selected schools. Participants 957 schoolchildren from government schools in Kuala Lumpur comprising the three major ethnic groups of Malay, Chinese and Indian children. Main outcome measures The severity of enamel opacities was assessed by the extent of buccal surface involvement. Normative treatment need was based on severity of opacities. Results Enamel opacities were found in 90.7 of subjects and 47.2 of teeth. Malays have the highest prevalence with Chinese the least. Although ethnic differences is statistically significant (p<0.01), the differences in prevalence between ethnicity is small. The most common type of defect was "diffuse opacities" (88.6 of subjects). Most subjects (70) showed bilateral distribution of diffuse opacities indicating a systemic disturbance. Posterior teeth were twice more commonly affected (p<0.05). The majority of opacities in anterior teeth (66.7) were minor, involving less than 1/3 of the labial surface. Only 0.6 of the whole sample required some form of aesthetic intervention. Conclusion Despite the high prevalence of enamel opacities, the degree of severity is very mild with only minimal aesthetic and public health concern.